(untitled) (Research, Society and Development, 2022)
Academic Leagues (LA) are fundamental in the teaching-learning process in various courses, seeking to meet the need for deepening in different themes, such as the subject of anatomy in medical courses. In this sense, understanding the relevance of ALs in the exchange of knowledge, the collaboration carried out between the Academic League of Anatomy of the Federal University of Mato Grosso do Sul and the Medical Student Nucleus on how to create and organize an academic league, so that this body could encourage the creation of LAs in Angola. Thus, the objective of this work is to report the experience lived by medical students from UFMS-CPTL in sharing knowledge about the foundation, management and development of academic leagues with Angolan academics from UNIPIAGET. This is an experience report based on the experience of Brazilian medical students participating in online meetings with Angolan academics on the functioning and importance of academic leagues for graduation and personal training. There were three meetings, via Google Meet, to address different perspectives regarding the academic experience within an LA, in addition to presenting the statute and work plans in order to provide models for UNIPIAGET students to be inspired and write their own leagues. The academic exchange allowed the sharing of fundamental knowledge for the creation and maintenance of an academic league, in addition to improving oratory skills and teamwork, bringing learning to the two groups involved.